Case Report: A case of surgical and enzyme replacement therapy for type I Gaucher disease complicating femoral shaft pathological fracture - Gao, Yang; Liu, Jia; Zhang, Zhijie; Sheng, Xinhao; Wang, Yuerong; Zhao, Xin; Ma, Huanzhi (Frontiers in Surgery, 2025)
Gaucher disease (GD) is an inherited lysosomal storage disorder caused by glucocerebrosidase (GCase) deficiency. A 35-year-old male patient was admitted to our hospital due to left thigh pain and restricted mobility for 10 h. Following comprehensive evaluations, the patient was diagnosed with GD complicated by a pathological fracture of the left femur. He has a known L444P mutation, a suspected pathogenic A170H mutation, and an A271 V mutation of uncertain significance not in GD databases. However, a potential association with the disorder cannot be excluded. We speculate that the patient's marked thrombocytosis may be related to the rare A170H and A271 V mutations. After an assessment, a decision was made to perform curettage of the left femoral lesion and open reduction internal fixation (ORIF) for the fracture. Postoperative management included ongoing enzyme replacement therapy. To date, case reports of GD patients undergoing ORIF for fractures are relatively rare, and the patient in this case harbored rare A170H and A271 V mutations. We report this case with the aim of sharing experience related to internal fixation for fractures in patients with GD, summarizing the specific phenotypes presented by specific gene mutation types, and providing a basis for the subsequent discovery of new gene mutations in GD.